Does Liquidity Management Affect Profitability in Selected Nigerian-Quoted Manufacturing Firms? - Abata, Matthew Adeolu; Migiro, Stephen Oseko (Journal of Economics and Behavioral Studies, 2016)
This study examined the nexus between liquidity management and profitability in selected Nigerian-quoted manufacturing firms. Many business failures have been recorded over the years due to inability to balance the link between liquidity and profitability. Descriptive research design was employed to analyze the data gathered from 2004 to 2014. The study found a positive relationship between credit policy, return on equity and return on capital employed. It equally found that operating cash flow and cash conversion cycle are negatively related to all the metrics of profitability. The study therefore recommends among others, that managers should strive to achieve a reasonable level of profit to optimize shareholders’ wealth and keep the firms in business. Also, managers should effectively manage account receivables and inventory at optimal level to avoid tie down liquid assets unnecessarily. Investors should pay close attention to firms’ operational cash flow in order to access their true state before committing their funds.